Conceptualizing and measuring subnational democracy across Indian states. Issue 7 (3rd October 2019) - Harbers, Imke; Bartman, Jos; van Wingerden, Enrike
ABSTRACT: India is often credited for its success as the world's largest democracy, but variation in subnational democracy across its states has not been systematically incorporated into scholarship on subnational regimes. This paper develops a conceptualization of subnational democracy based on four constitutive dimensions – turnover, contestation, autonomy and clean elections – and introduces a comprehensive dataset to measure each of the dimensions between 1985 and 2013. The inclusion of India – an older parliamentary democracy with a centralized federal system – broadens the universe of cases for the study of subnational regimes, and reveals variation across constitutive dimensions that has not yet been theorized. The paper shows that threats to subnational democracy come from multiple directions, including the central government and non-state armed actors, that subnational variation persists even decades after a transition at the national-level, and that subnational democracy declines in some states in spite of the national democratic track record.